2010
DOI: 10.1051/0004-6361/201014383
|View full text |Cite
|
Sign up to set email alerts
|

Low-resolution spectroscopy of main sequence stars belonging to 12 Galactic globular clusters

Abstract: Context. Globular clusters show star-to-star abundance variations for light elements that are not yet well understood. The preferred explanation involves a self-enrichment scenario, within which two subsequent generations of stars co-exist in globular clusters. Observations of chemical abundances in the main sequence and sub-giant branch stars allow us to investigate the signature of this chemically processed material without the complicating effects caused by stellar evolution and internal mixing. Aims. Our m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
164
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(176 citation statements)
references
References 196 publications
(274 reference statements)
12
164
0
Order By: Relevance
“…To these 46 spectra observed with Magellan, we added 47 other MS and SGB spectra from Pancino et al (2010) observed with the FORS2 multi-object spectrograph on the ESO VLT at the Paranal Observatory in Chile. We refer the reader to that paper for details of the FORS2 observations.…”
Section: Observations and Spectroscopic Reductionsmentioning
confidence: 99%
See 3 more Smart Citations
“…To these 46 spectra observed with Magellan, we added 47 other MS and SGB spectra from Pancino et al (2010) observed with the FORS2 multi-object spectrograph on the ESO VLT at the Paranal Observatory in Chile. We refer the reader to that paper for details of the FORS2 observations.…”
Section: Observations and Spectroscopic Reductionsmentioning
confidence: 99%
“…We refer the reader to that paper for details of the FORS2 observations. We reduced our data following the procedure described in Pancino et al (2010). For the data pre-reduction, we used the standard procedure for overscan correction and bias-subtraction with the routines available in the noao.imred.ccdred package in IRAF 2 .…”
Section: Observations and Spectroscopic Reductionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Star-to-star differences in the C and N abundances have been known for decades in GCs (see, e.g., Osborn 1971;Norris 1981;Martell & Smith 2009;Pancino et al 2010), with the detection of CN-weak and CN-strong stars. In recent years the use of high-resolution spectroscopy coupled with large samples of GC stars has established that old, massive GCs, both in our Galaxy (Carretta et al 2009; and in the Local Group satellites (Mucciarelli et al 2009), show star-to-star variations in some light elements: intrinsic scatters of Na and O abundances have been observed in all the GCs, variations of Al abundances in most of them, while star-to-star scatters in Mg abundances have been found only in some peculiar clusters.…”
Section: Introductionmentioning
confidence: 99%